Japan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2003)
The Selected Issues paper analyzes the health of the corporate sector, areas of vulnerability, and the effect of corporate restructuring in Japan. It reviews the deflation and associated economic problems of Japan, demonstrates the impact of fiscal policies on public debt, and estimates the expenditure and revenue adjustments needed to restrain the growth of debt. It also analyzes the issues in the Japanese labor market, structural developments, changes in the behavior of stakeholders, policy issues on employment insurance, and the social safety net.